Outcomes in Conservative Versus Surgical Treatments in Ludwig’s Angina Cases: A Comparative Study: Conservative Versus Surgical Outcomes in Ludwig’s Angina - Imam, Fatima; Shahzad, Muhammad; Chachar, Zaheer Hussain; Madhuri, Maya; Bashir, Uzma; Gaju, Junaid Naveed; Shams, Salman (Pakistan Journal of Health Sciences, 2025)
Rapid airway impairment brought on by Ludwig's angina may require careful antimicrobial treatment or surgery. Objective: To compare the airway compromise and hospital stay in conservative versus surgical approach in cases with Ludwig's Angina. Methods: This experiment was conducted at Liaquat University using a non-probability consecutive sampling technique to recruit 76 patients, aged 18 to 40, diagnosed with early-stage Ludwig’s angina without airway obstruction. Quasi-experimental study. There were 38 patients in each group, and participants were randomized to either the surgery group or the conservative treatment group. Outcomes such as airway compromise and length of hospital stay were recorded and compared between groups using t-tests and Fisher’s exact tests. Findings: The conservative group's mean age was 30.58 ± 5.52 years, while the surgical group's was 31.34 ± 5.92 years. There were 11 females (28.95%) and 27 males (71.05%) in the conservative group and 8 females (21.05%) and 30 males (78.95%) in the surgical group. There was a statistically significant difference (p < 0.001) in the length of hospital stay between the surgical group (6.97 ± 1.10 days) and the conservative group (5.05 ± 0.89 days). Five patients (13.16%) in the surgical group and three patients (7.89%) in the conservative group experienced airway impairment; however, this difference was not statistically significant (p = 0.706). Conclusion: Conservative treatment, being less invasive, can be effective in mild cases, leading to shorter hospital stays and a reduced risk of airway compromise.